Case Report: A rare case of community-acquired Roseomonas mucosa sepsis that presented with persistently normal host-response biomarkers - Xu, Xiaomei; Li, Ying; Huang, Xin (Frontiers in Immunology, 2025)
Community-acquired Roseomonas mucosa sepsis can lead to significant morbidity and mortality if not diagnosed promptly. We report a case of a 59-year-old woman with community-acquired Roseomonas mucosa sepsis who presented with persistent fever progressing to septic shock, despite repeatedly negative host-response biomarker results. Initial metagenomic analysis of peripheral blood suggested Pseudomonas aeruginosa infection. However, a peripheral blood culture identified Roseomonas mucosa as the causative pathogen. She was cured after switching to meropenem according to blood cultures and antimicrobial susceptibility testing.